Implementation Of Swot Analysis: Case Study Of Crot-De Business (Crocodile Tongue Pomade) - Muhammad Alvinza Chairyan; Ari Zulfi Kharisma; Muhammad Hanafi Lubis; Dhea Octa Yolanda; Suhelni Suhelni (JASc (Journal of Agribusiness Sciences), 2019)
The term pomade comes from French, which is pommade, which means 'ointment'. The use of pomades dates back to the 1800s. During this century, and the main ingredients used in making pomade were bear fat. Pomade is a male cosmetic product that is in great demand, especially teenagers. Men's hairstyles are various, but the most favorite hairstyles are undercut and pompadour, this hairstyle will be more beautiful when using pomade. However, pomade on the market contains chemicals that can cause side effects for hair, and also have a price that is quite draining. Therefore, we brought up a new innovation herbal product, namely CROT-DE (Crocodile Tongue Pomade). Pomade CROT-DE products are prepared from basic ingredients, namely Aloe Vera. Aloe vera is processed into a beauty product, which is commonly used by men as a cosmetic product for hair that is used so that their hair is smooth, cool and confident. The research method used was using a qualitative approach. Qualitative research is research that intends to understand the phenomenon of what is experienced by the subject of research such as behavior, perception, motivation, actions and others holistically and by way of description in the form of words and language, in a special context that is natural and with utilizing various natural methods. From the definition above, it can be concluded that the researcher is trying to understand the phenomenon experienced by the subject, be it behavior, perception, motivation, etc. This business has a huge opportunity because many pomade products on the market still use chemicals. Of course this refers to the creation of CROT-DE pomade products with natural ingredients from aloe vera. Therefore, in this article I will discuss the SWOT analysis. SWOT analysis is a strategy in evaluating strengths, weaknesses, opportunities, and threats which can be applied generally to business activities. SWOT analysis is a strategic planning method consisting of aspects of the product (strength), product Weaknesses, product opportunities, and product threats. First, strength is the raw materials needed in making Pomade products that are very easy to obtain. Second, the weakness strategy (weakness) is that the pomade product is not widely known by the public. Third, the opportunity strategy is the absence of Pomade products that use natural ingredients. Fourth, the threat strategy is to have a fairly heavy competitor whose products are first known in the market